The mitigative effect of lotus root (Nelumbo nucifera Gaertn) extract on acute alcoholism through activation of alcohol catabolic enzyme, reduction of oxidative stress, and protection of liver function - Yang, Zihan; Gao, Yuan; Wu, Weijie; Mu, Honglei; Liu, Ruiling; Fang, Xiangjun; Gao, Haiyan; Chen, Hangjun (Frontiers in Nutrition, 2023)
Lotus root (Nelumbo nucifera Gaertn) is a common medicinal-food dual-use vegetable. In this study, the effects of lotus root extract on acute alcoholism were investigated. Results indicated the methanol extract of lotus root showed the highest activation rate of ethanol dehydrogenase in vitro (18.87%). The 433 compounds of lotus root methanol extract were identified by UPLC-QTOF-MS/MS based metabolomics analysis. Then 109 active ingredients with achievable oral doses and drug-like properties were explored using the TCMSP platform. Bioinformatics analysis indicate that there were 224 intersectioning targets between lotus root extract and acute alcoholism. KEGG enrichment analysis shows that lotus root extract may play a role in treating acute alcoholism by intervening with the neuroactive ligand-receptor interaction pathway. The protein-protein interaction network (PPI) analysis found that HSP90AA1, MAPK1 and STAT3 played a key role in lotus root extract-modulated PPI networks. Molecular docking showed that (7R, 8S)-dihydrodihydrodipine cypressol had the best binding ability with MAPK1. Experiments in mice indicate that lotus root extract improved the activity of liver alcohol dehydrogenase (ADH), acetaldehyde dehydrogenase (ALDH), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX), increase glutathione (GSH) and reduce malondialdehyde (MDA) levels, decrease glutamate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (AKP) in the serum of mice with acute alcoholism, and accelerate the metabolic rate of alcohol after drinking. This study reveals the mechanism of lotus root to alleviate acute alcoholism, which provides a basis for further research on functional foods using lotus root and offers new possibilities for the treatment of acute alcoholism.